EVALUASI EFEKTIVITAS SISTEM INFORMASI DENGAN PENDEKATAN UTILITY SYSTEM (Studi Kasus : Politeknik Sawunggalih Aji) - Singgih Arif Widodo; Bambang Soedijono; Andi Sunyoto (JURNAL EKONOMI DAN TEKNIK INFORMATIKA, 2018)
This research aimed to evaluate information system Polytechnic Sawunggalih Aji by using utility systemapproach. Utility system approach to evaluate information system from the point of the system effectiveness, firstlyproposed by Kendall. This approach captured the perception of the system based on 6 points of view, which arepossession, form, place, time, actualization and goal, as well as the scale of measurement using a likert scale and SPSSsoftware. This study uses a research instruments with a likert scale questionnaire. The results showed how good thequality of the information system Polytechnic Sawunggalih Aji, and any item of utility system that contributed the most toimproving the quality of the system, as well as proposals that may be submitted to the management of information systemto develop more qualified information system.Keywords: Evaluation, Information system, effectiveness, Utility Approach, SPSS.